Fish, fans and hydroids: host species of pygmy seahorses - Reijnen, B; van der Meij, S; van Ofwegen, L (Pensoft Publishers, 2011)
An overview of the octocoral and hydrozoan host species of pygmy seahorses is provided based on literature records and recently collected field data for Hippocampus bargibanti, Hippocampus denise and Hippocampus pontohi. Seven new associations are recognized and an overview of the so far documented host species is given. A detailed re-examination of octocoral type material and a review of the taxonomic history of the alcyonacean genera Annella (Subergorgiidae) and Muricella (Acanthogorgiidae) are included as baseline for future revisions. The host specificity and colour morphs of pygmy seahorses are discussed, as well as the reliability of (previous) identifications and conservation issues.